A Review on Histological Changes of Follicle in the Cow - Safi, Mohammad Asif (Journal of Natural Sciences – Kabul University, 2022)
The development of female sex cells is closely linked to the follicles, which include the primary follicle and follicular cells. Follicular cells surround the primary follicle, and follicles are named based on their developmental stages. The primordial follicle forms before birth through mitotic division of inner epithelial cells in the ovarian cortex. The primary follicle contains a primary oocyte surrounded by simple cubic epithelial follicular cells. The secondary follicle includes an early oocyte surrounded by stratified epithelial follicular cells. The tertiary follicle consists of a secondary oocyte surrounded by stratified epithelial cumulus cells. Understanding follicular development is critical for successful insemination in cows. This article explains the histological changes occurring during follicular development.